2016
DOI: 10.1097/ypg.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptor 1B gene associated with hyperglycemia in bipolar disorder

Abstract: Bipolar patients are at a higher risk of developing metabolic disorders. Cardiovascular morbidity and mortality is twice the rate reported in the population. Antipsychotic medication increases the risk of metabolic abnormalities. However, bipolar disorder and schizophrenia have a similarly increased mortality from cardiovascular causes of death, although bipolar patients medicate with antipsychotic drugs to a much smaller extent than schizophrenic patients. Bipolar disorder and schizophrenia share substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Despite a lack of significant role of glucose dysregulation in predicting the time to next admission in our study, its demanding role in modulating the illness course of bipolar disorder is prominent. Several genetic studies have revealed the associations of glucose/insulin metabolism-related genes and the development of bipolar disorder [ 21 - 24 ]. Supporting evidence has also been reported in studies investigating the biochemical profiles in patients with bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of significant role of glucose dysregulation in predicting the time to next admission in our study, its demanding role in modulating the illness course of bipolar disorder is prominent. Several genetic studies have revealed the associations of glucose/insulin metabolism-related genes and the development of bipolar disorder [ 21 - 24 ]. Supporting evidence has also been reported in studies investigating the biochemical profiles in patients with bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%